Merambah Etika Protestan dan Sosiologi Nilai Max Weber “Korelasi Antara Calvinisme dengan Spirit Kapitalisme” - Marde Christian Stenly Mawikere; Sudiria Hura (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study traces the traces of the Sociology of Religion theory (classic) from Max Weber which he described in his best-selling book entitled "The Protestant Ethic and the Spirit of Capitalism". The research was carried out by conducting a "book review" on the substance and ideas of Max Weber regarding the relationship between religious values ​​adopted by the adherents' work ethic. In this case Weber highlights the phenomenon of capital growth/capitalism in Europe which is the result of the work ethic of Protestants, especially the Calvinists there. Thus the Sociology of Religion recommended by Max Weber includes the relationship between religion and society which can also be called "the sociology of values". Therefore, values ​​become a driving factor in the participation and work ethic of humans individually and in groups created in development, namely economic growth and other aspects holistically